Perancangan Green Agrotourism Hotel Dengan Aplikasi Sistem Akuaponik di Kota Batu - Natasya Angelina Terunajaya; Purnama Esa Dora Tedjokoesoemo; Muhammad Taufan Rizqy (Intra, 2019)
The large number of investors who want inn in hotel forms is not in line with the Batu city’s branding: Shining Batu which promotes education and agriculture programs in addition to its tourism. Although there are still many educational and agricultural tourism destinations that are being developed, Batu City government has adopted a policy to ban the construction of hotels, especially three-star hotels. This design will provide alternative hotel facilities by combining three images of Batu City including tourism, education, and agriculture in one building, but still prioritize the impact on the environment. The design method consists of seven stages, namely understand, observe, point of view, ideate, prototype, test, and implementation. The result of the design is an agrotourism hotel building with an aquaponic application system with the concept of Revan with facilities such as lobby, restaurant, guest bedroom, and aquaponic garden.